Pengelolaan Pembelajaran PKN Berkarakter Disiplin Di MTs N 1 Wonogiri - Darmawan, Tjutjuh; , Dr.Suyatmini,SE.,M.Si; , Dr. Sabar Narimo (2016)
The purpose of this study: describes the planning, execution, and evaluation of learning management Civics MTs characteristic discipline in Wonogiri. The location of research at MTs 1 Wonogiri. This type of research is qualitative research with case study approach. Data collection techniques using observation, interviews, and document analysis methods. Data analysis techniques in this study using triangulation. The results of this study are characterized Civics learning management planning discipline at MTs 1 Wonogiri begins with the Civics curriculum development, syllabus development civics, civics lesson plan development, development of resources, integration of disciplines characters in Civics lesson planning; implementation of learning management discipline characterized Civics at MTs 1 Wonogiri includes the preparation of Civics learning facilities and infrastructure, implementation of learning civics, civics learning classroom management, instructional media use Civics, learning method Civics, integration of the character of discipline in the implementation of learning civics; evaluation of learning management discipline characterized Civics at MTs 1 Wonogiri to assess the success of this program, overall evaluation kontinnyu each end of the school year. Having hosted learning management discipline characterized Civics increased discipline of teachers and students in the learning process. However, in the evaluation of teacher learning tend to emphasize the cognitive aspects, and less attention to the affective and psychomotor aspects.